Suicide Response in American Muslim Communities: A Community Case Study - Belal Zia; Kamal Suleiman; Osama El-Gabalawy; Rania Awaad (Journal of Muslim Mental Health)
This community case study describes the experiences of two neighboring Muslim communities in the United States, following respective incidents of suicide. Case summaries are first presented to contextualize the community response to the suicides. Subsequently, the discussion highlights relevant cultural and religious factors that impacted the responses of mosque leadership, mental health professionals, and the communities at large. Concerns related to the deceased’s afterlife, community connectedness, privacy, shame, and communication barriers were prominent in each case and shaped the courses of response. The COVID-19 pandemic and divergent responses to external support played significant roles in creating disparate outcomes in these communities. The discussion emphasizes the need for dissemination of evidence-based, religiously grounded, and culturally competent curricula for implementing mental health awareness programming and long-term suicide prevention efforts. Insights about cultural and religious factors influencing community responses were derived from the described cases in this paper and informed the development of a comprehensive suicide prevention, intervention, and postvention manual and training program tailored for Muslim communities.